DEVELOPMENT AND VALIDATION OF NOVEL REVERSE-PHASE HIGH-PERFORMANCE LIQUID CHROMATOGRAPHY METHOD FOR SIMULTANEOUS ESTIMATION OF ANDROGRAPHOLIDE AND ALOE-EMODIN - PATIL, RASHMI; JAISWAR, UTTARA; JAIN, VANDANA (Asian Journal of Pharmaceutical and Clinical Research, 2020)
Objective: The study aims to develop and validate a novel reverse-phase high-performance liquid chromatographic method for simultaneous estimation of andrographolide and aloe-emodin in herbal formulation and validate as per the International Conference on Harmonization (ICH) guidelines. Methods: The analysis was carried on a Shimadzu LC Prominence-i 2030 model with the Lab Solution software. The column used for separation was Prontosil C18 (250×4.6 mm, 5 μ), with a mobile phase consisting of acetonitrile and 0.05% orthophosphoric acid (45:55), at a flow rate of 1 ml/min, column temperature was maintained at 28°C and effluents were monitored at 225 nm. The injection volume was 10 μl. Results: The retention time of andrographolide and aloe-emodin was found to be 4.57±0.2 min and 12.29±0.2 min, respectively. The markers were resolved using linear responses that were obtained in concentration ranges of 0.5–60 μg/ml with correlation coefficient (r2) of 0.9992 and 0.999 for andrographolide and aloe-emodin, respectively. The precision results were found to be satisfactory, which indicates that the method is precise. The recovery values lie in the range of 98–120% indicating the accuracy of the method. Conclusion: A novel, simple, accurate, precise, and robust reverse-phase high-performance liquid chromatography method was developed for the simultaneous estimation of andrographolide and aloe-emodin. The developed method can be used for analysis of the formulations containing these phytoconstituents.